What is extreme about Mises' extreme apriorism? - Scott Scheall (Duke University, Center for the History of Political Economy (CHOPE), 2016)
There is something extreme about Mises' apriorism, namely, his epistemological justification of the a priori element(s) of economic theory. His critics have long recognized and attacked the extremeness of Mises' epistemology of a priori knowledge. However, several of his defenders have glossed or ignored what is (and what has long been recognized by his critics to be) extreme about Mises' apriorism. Thus, the argument is directed less against Mises than those contributions to the secondary literature that assert his methodological moderation while glossing or plainly ignoring what the most prominent critics have found extreme about Mises' apriorism. Defending Mises as a merely moderate apriorist because he held only a narrow part of the foundation of economics to be a priori is a straw-man defense against criticisms of his apriorism as epistemologically extreme.
Keywords: B25; B31; B41; B53; 330; Ludwig von Mises; Austrian economics; methodology; apriorism